Effect of influent COD and TN on ship sewage treatment by using an aerobic-anaerobic membrane bioreactor (O/A-MBR). Issue 1 (February 2020) - Zhang, Kun; Wang, Yiquan; Cai, Yuhang; Sun, Peiqi; Li, Jianing; Wang, Gaoshuai; Shi, Yue
Abstract: The implementation of the latest International Maritime Organization (IMO) emission standards places stringent requirements on ship domestic wastewater discharges. In this study, an aerobic-anaerobic membrane bioreactor (O/A-MBR) was used to investigate the effect of influent COD and TN on ship sewage treatment. The results show that the lower volume load will affect the growth of the organism, and then affect the removal efficiency of COD. The increase of volume load is beneficial to the removal of COD, but the relatively high load will affect the removal of TN. Throughout the process, the O/A-MBR reached high COD and TN removal efficiencies with average values of 87.46% and 85.83%, respectively, and the best volume load range is obtained based on this experiment. It indicates that the novel MBR leads to good pollutants degradation effort and has great potential in practical ship domestic sewage treatment.